Resolution Of The Board Of Directors Of The Central Bank Of Egypt (CBE) No. 1010 Of The Year 2013 In Its Session Held On May 21st, 2013 On The Limitations Of Exercising Bancassurance By Banks = البنك المركزى المصرى أمانة مجلس الإدارة قرار مجلس إدارة البنك المركزى رقم 1010 لسنة 2013 بجلسته المنعقدة فى 21 مايو 2013 بشأن ضوابط مزاولة البنوك لنشاط التأمين المصرفى - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.